Implant Discontinuation Rate Among Teenage Pregnancy in 2015-2017 - สันติภาพ มนต์ชัย (Journal of Preventive Medicine Association of Thailand, 2018)
Teenage pregnancy is one of the major problems in Thailand. In 2017, there were 54.1 live births in every 1,000 adolescents (15-19 years) in Saraburi province, which is higher than the Thailand expected rate. Thai government has launched a campaign to reduce teenage pregnancy rate by offering free contraceptive implant for the under 20 years pregnant women. The aims of this study were to assess the discontinuation rate of contraceptive implant of teenage pregnant women who initiated implantation at Saraburi hospital postpartum unit after one year, and to study the factors influencing the contraceptive implant discontinuation and the recurrent pregnancy. The study was retrospectively conducted in teenage pregnant women who delivered at Saraburi hospital during May 2015 to February 2017. Only 121 out of 489 under 20 years pregnant women were included in this study since the others were unable to be contacted by phone. The results showed that the implant discontinuation rate was 1.7% (2 out of 121). Weight gain and spot bleeding were the major problems influencing the implant discontinuation. On the contrary, no recurrent pregnancy was found due to switching from implant to combined oral contraceptive pills. However, the informing about side effects of the contraceptive implants was not done. So the healthcare providers should explain about the side effects in order to pursue more adherence rate. Ultimately, endeavor to achieve a high 5-year period continuation rate is necessary for ensuring the utmost benefit out of the government budget for this implant campaign.